Fighting COVID-19: What's in a Name? - Thomas Kun Pak; Aline Sandouk; Phuong Le (University Library System, University of Pittsburgh, 2020)
While the COVID-19 virus has infected over 3 million people in the United States of America, Asian Americans face unique unfair treatment due to COVID-19. In America, many anti-Asian incidents have been reported, and the FBI warns of increased hate crimes to Asian Americans due to COVID-19. Americans and high-level politicians use inappropriate names, such as "Chinese Virus," for the COVID-19 virus, which fuels racism and xenophobia. In this Experience piece, we discuss the harm of referring to the COVID-19 virus based on the geographic location where it was first identified.